Interleukin-17A attenuates photoreceptor cell apoptosis in streptozotocin-induced diabetic mouse model. Issue 6 (1st June 2022) - Zhu, Minqi; Gao, Shuang; Gao, Sha; Wang, Yanuo; Li, Na; Shen, Xi
ABSTRACT: Diabetic retinopathy (DR) represents an important microvascular complication of diabetes, which is the top etiology of vision impairment worldwide. Although interleukin (IL)-17A is increasingly implicated in DR development, the underlying cellular mechanisms remain poorly defined. This work aims to evaluate IL-17A levels in the retina of streptozotocin (STZ)-induced diabetic mice and elucidate their potential roles. We found IL-17A was upregulated in diabetic retina after intraperitoneal injection of STZ and high-glucose (HG)-cultured primary Müller cells. IL-17A knockout (IL-17A −/− ) downregulated glial fibrillary acidic protein (GFAP) and inhibited the conversion of proneurotrophin-3 (proNT-3) to mature NT-3 in retinal specimens from diabetic mice as well as in Müller cells cultured under HG conditions. Induced apoptosis and upregulated Bax and cleaved caspase-3 were observed in retinal specimens from IL-17A −/− diabetic mice and photoreceptor (661 W) cells after co-culture with IL-17A −/− Müller cells. Moreover, RNA interference-induced gene silencing of tyrosine kinase C receptor (TrkC) in 661 W cells reversed the anti-apoptotic effect of IL-17A under HG conditions. Taken together, our findings suggest that IL-17A/NT-3/TrkC axis regulation suppresses apoptosis in photoreceptor cells, providing a new treatment strategy for DR. GRAPHICAL ABSTRACT: uf0001